Seed improvement, production and quality of vegetable crops in Peninsular Malaysia - Thai, Teng Yeew; Chin, Hoong Fong (International Society for Horticultural Science, 1981)
Seed improvement of vegetable crops in Peninsular Malaysia is mainly geared towards introduction, selection and evaluation of existing local cultivars and introduced varieties. Some effort is also presently devoted to systematic breeding to improve vegetable crop yield.